Colonial Residence now a Museum (La casa del Alfeñique Puebla, Pue, México) - (:unkn) unknown (Printed in Mexico, 2009)
This was the home of Ignacio Morales, a wealthy ironworker. The house was built in 1791 which is now the Regional Museum of Puebla, Mexico. Affixed to the postcard are a 22 cents and 5 cents British Honduras stamps. Addressed to Mr. and Mrs. Clifford Smith, Bayswater, London, England.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Mexico; Museums--Mexico; Buildings--Mexico; 1967